Effect of Polyarginine Peptide R18D Following a Traumatic Brain Injury in Sprague-Dawley Rats - Li Shan Chiu, PhD; Ryan S. Anderton, PhD; Vince W. Clark, MSc; Jane L. Cross, PhD; Neville W. Knuckey, MBBS; Bruno P. Meloni, PhD (Elsevier, 2020)
ABSTRACT: Background: Despite extensive studies, there are still no clinically available neuroprotective treatments for traumatic brain injury. Objectives: In previous studies we demonstrated beneficial treatment effects of polyarginine peptides R18 (18-mer of arginine; 300 nmol/kg) and R18D (18-mer of D-arginine; 1000 nmol/kg) in a rat model of impact-acceleration closed-head injury. Methods: We examined the efficacy of R18D when intravenously administered at a low (100 nmol/kg) and high (1000 nmol/kg) dose, 30 minutes after a closed-head injury in male Sprague-Dawley rats. Results: At postinjury day 3, treatment with R18D at the high dose significantly reduced axonal injury (P = 0.044), whereas the low-dose treatment of R18D showed a trend for reduced axonal injury. Following assessment in the Barnes maze, both doses of R18D treatment appeared to improve learning and memory recovery compared with vehicle treatment at postinjury days 1 and 3, albeit not to a statistically significant level. Rotarod assessment of vestibulomotor recovery did not differ between R18D and the vehicle treatment groups. Conclusions: R18D modestly decreased axonal injury only at the highest dose used but had no significant effect on functional recovery. These findings warrant further studies with additional doses to better understand peptide pharmacodynamics and provide information to guide optimal dosing.